Physiological, Immunological and biochemical effects of the fungus aspergillus Niger toxicity in albino male rats (Eurasian Medical Research Periodical, 2022)
This research was planned to investigate the effect of the mycotoxin created by the fungal species Aspergillus Niger on experimental animals (albino male rats) to test the effects on certain biochemical and immunological variables